Implementasi matematika di era teknologi: The Role of Cryptography in Securing Messages - Nuryanawati, Ita (Maliki Interdisciplinary Journal, 2024)
Messages are a common aspect of our interactions, and various channels are used to convey messages. For messages that require special confidentiality, special security measures are also required. Cryptography, which is based on mathematical principles, is an effective way to overcome this challenge. The focus of this paper is to understand cryptographic concepts and techniques that rely on mathematical aspects in protecting messages. The success of this security system is closely related to the mathematical complexity that takes a long time for unauthorized parties to dismantle it. Therefore, the application of mathematics in cryptography allows messages to be efficiently secured in a digital environment full of potential threats. Thus, confidential and sensitive messages can be communicated without risk of leakage or harmful manipulation.